Instituições, modelos de estado e o sistema previdenciário brasileiro - Costa, Rafael Milani da (2012)
Several neoliberal arguments have been used to criticize the Brazilian social security system (specially the deficit) such as the transformation in the age structure, increasing social safety net, the real increases in the minimum wage, the informal labor market and low growth economic, which manifest themselves at different levels, among others. It is argued that these discussions are based on the appearance of the problem and that the discussion is actually tied to the state model and it's role in the economy This work aims to analyze the Brazilian social security system and it's relationship with the model state that the country has chosen to follow. For this, we use the theoretical principles developed by the institutionalism school of economics, with emphasis on the concepts of institutions, institutional environment, institutional change, formal rules and pressures for change. The period of analysis covers the years between 1889 and 2011, a period that covers the vast majority of measures taken in relation to social security in Brazil. For the development work was performed literature review on the institutionalist school, the legal documents pertaining to the subject and the historical evolution nationwide, especially for the Brazilian social security system. We identified two major changes in the institutional environment in the country during the time cutting proposed: the passage of a Liberal State (1889-1929), even if not completely, to a Welfare State (1930-1979), and the fall of the latter model, making room for the dominance of the principles defended by the Neoliberal State (1980-2005). We analyze one last period between the years 2006 e 2011, which stands out for discussion around the role of the state in the economy. The examination of social security legislation shows that they have changed, a greater or larger degree, the perception according to the characteristics and the economic interests of each state model adopted in the country.